The effects of emotion regulation strategies on the pain experience: a structured laboratory investigation. Issue 5 (May 2015) - Hampton, Amy J. D.; Hadjistavropoulos, Thomas; Gagnon, Michelle M.; Williams, Jaime; Clark, David
Abstract : Abstract: Although emotion regulation modulates the pain experience, inconsistencies have been identified regarding the impact of specific regulation strategies on pain. Our goal was to examine the effects of emotion suppression and cognitive reappraisal on automatic (ie, nonverbal) and cognitively mediated (ie, verbal) pain expressions. Nonclinical participants were randomized into either a suppression (n = 58), reappraisal (n = 51), or monitoring control (n = 42) condition. Upon arrival to the laboratory, participants completed the Emotion Regulation Questionnaire, to quantify self-reported suppression and reappraisal tendencies. Subsequently, they completed a thermal pain threshold and tolerance task. They were then provided with instructions to use, depending on their experimental condition, suppression, reappraisal, or monitoring strategies. Afterward, they were exposed to experimentally induced pain. Self-report measures of pain, anxiety, and tension were administered, and facial expressions, heart rate, and galvanic skin response were recorded. The Facial Action Coding System was used to quantify general and pain-related facial activity (ie, we defined facial actions that occurred during at least 5% of pain stimulation periods as "pain-related actions"). Reappraisal and suppression induction led to reductions in nonverbal and verbal indices of pain. Moreover, self-reported tendencies to use suppression and reappraisal (as measured by the Emotion Regulation Questionnaire) did not interact with experimental condition in the determination of participants' responses. Results suggest that consciously applying emotion regulation strategies during a painful task can moderate both cognitively mediated (eg, verbal) and automatic (eg, facial activity) expressions of pain. Abstract : Supplemental Digital Content is Available in the Text.Within the context of an experimental study, reappraisal and suppression induction (as emotional regulation strategies) led to reductions in self-reported pain and nonverbal expressions.